2017
DOI: 10.1007/s00605-017-1047-9
|View full text |Cite
|
Sign up to set email alerts
|

Univoque bases and Hausdorff dimension

Abstract: Given a positive integer M and a real number q > 1, a q-expansion of a real number x is a sequence (c i ) = c 1 c 2 . . . with (c i ) ∈ {0, . . . , M} ∞ such that It is well known that if

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Since the differences amongÛ , U L , U R = U and U are at most countable, the dimensional results obtained in this paper for U = U R also hold forÛ , U L and U . Now we recall from [21] the following characterizations of the left and right bifurcation sets U L and U R respectively. where B n (X) denotes the set of all length n subwords occurring in elements of X, and #A denotes the cardinality of a set A.…”
Section: Introductionmentioning
confidence: 99%
“…Since the differences amongÛ , U L , U R = U and U are at most countable, the dimensional results obtained in this paper for U = U R also hold forÛ , U L and U . Now we recall from [21] the following characterizations of the left and right bifurcation sets U L and U R respectively. where B n (X) denotes the set of all length n subwords occurring in elements of X, and #A denotes the cardinality of a set A.…”
Section: Introductionmentioning
confidence: 99%
“…In the sequel, Sidorov [14] used ergodic theoretical methods to prove that for all q ∈ (1,2) almost all x ∈ (0, 1/(1 − q)) have such an expansion. Moreover, Glendinning and Sidorov [7] proved that there always exist (at least countably many) reals having a unique expansion if q > G. Nowadays, especially dimensional theoretical aspects of expansions of reals numbers in non-integer bases are studied; see, for instance, [1,9,10]. In this paper, we introduce non-uniform expansions of real numbers, which may be viewed as expansions with respect to two non-integer bases.…”
Section: Introductionmentioning
confidence: 99%
“…In [25] the same authors studied the topological properties of U , and showed that its closure U is a Cantor set. Recently, Kong et al proved in [28] that for any q ∈ U we have (1.3) dim H (U ∩ (q − δ, q + δ)) > 0 for any δ > 0.…”
Section: Introductionmentioning
confidence: 99%